Hi there,
Take y from first equation and use it / substitute it into the second equation:
-2x + 8 = x - 1, so 3x = 9, therefore x = 3.
Then y = x - 1 = 3 - 1 => y = 2.
Solution is (3,2).
A quick check: 2 = -2*3 + 8, true, and 3 = 2 - 1, also true.
Green eyes.
Answer: The answer is NO
Step-by-step explanation:
(680 * d) - (960 * d) + 52000 =
is the equation, i’m not sure what the total answer is though.
Julianne will start making a profit on day 55 or 54. Check again, because it could be either.
Please mark brainliest , thank you , and have a great day .
H1 (t) = 196 - 16 t-squared. / / / H2 (t) = 271-16t-squared. / / / In each function, 't' is the number of seconds after that ball is dropped. / / / Each function is only true until the first time that H=0, that is, until the first bounce. Each function becomes very complicated after that, and we would need more information in order to write it.
Answer:steepness
Step-by-step explanation: